Results of the orthoradial technique vs parallel technique in the identification of canals of upper first premolars and lower first molars - Pablo Sebastián Vásconez Ponce; Martín Nicolás Proaño Santamaría; Catalina del Rosario Boada Zurita; Tiana Mayerlin Rojas Uribe (Medisur)
Foundation: advances in imaging and its implementation in Dentistry allow for better treatments. Objective: to describe the results of the orthoradial technique vs parallel technique in the identification of upper first premolars canals and lower first molars. Methods: observational, descriptive and cross-sectional study in patients in need of root canal treatment of upper first premolars or lower first molars, who attended the Dental Care Unit of the Andes Regional Autonomous University from April to August 2019. The sample consisted of 62 patients, separated into two upper premolar groups (n=30) or lower first molars (n=32) and both into two other groups according to the technique used (parallel technique and orthoradial technique). Results: in the upper first premolars, the orthoradial technique showed better results than the parallel technique to obtain accurate images (100% vs. 20%). In the lower first molars, the orthoradial technique showed superior results to the parallel technique for the mesiolingual canal (93.75% vs 31.25%) and distolingual canal (31.25% vs 12.5%). Root elongation predominated in the orthoradial technique (n=8), as did dental overlap (n=10). Conclusions: the orthoradial technique showed superior results when locating both the buccal and palatine canal in the upper first premolars and for the mesiolingual canal and the distolingual canal. Root elongation was observed to a greater extent in the orthoradial technique, as was dental overlap.